Retinoic Acid–Inducible Gene I Activation Inhibits Human Respiratory Syncytial Virus Replication in Mammalian Cells and in Mouse and Ferret Models of Infection. (21st July 2022) - Schwab, Lara S U; Farrukee, Rubaiyea; Eléouët, Jean-François; Rameix-Welti, Marie-Anne; Londrigan, Sarah L; Brooks, Andrew G; Hurt, Aeron C; Coch, Christoph; Zillinger, Thomas; Hartmann, Gunther; Reading, Patrick C
Abstract: Infections caused by human respiratory syncytial virus (RSV) are associated with substantial rates of morbidity and mortality. Treatment options are limited, and there is urgent need for the development of efficient antivirals. Pattern recognition receptors such as the cytoplasmic helicase retinoic acid–inducible gene (RIG) I can be activated by viral nucleic acids, leading to activation of interferon-stimulated genes and generation of an "antiviral state." In the current study, we activated RIG-I with synthetic RNA agonists (3pRNA) to induce resistance to RSV infection in vitro and in vivo. In vitro, pretreatment of human, mouse, and ferret airway cell lines with RIG-I agonist before RSV exposure inhibited virus infection and replication. Moreover, a single intravenous injection of 3pRNA 1 day before RSV infection resulted in potent inhibition of virus replication in the lungs of mice and ferrets, but not in nasal tissues. These studies provide evidence that RIG-I agonists represent a promising antiviral drug for RSV prophylaxis. Abstract : Pretreatment of human, mouse, or ferret airway cell lines, as well as intravenous injection of mice and ferrets, with a synthetic retinoic acid–inducible gene I agonist resulted in reduced susceptibility to subsequent respiratory syncytial virus infection.